Lexeme „gay” as a linguistic sign of strangeness in the discourse of ultra-conservative ortodox monarchists in Russia - Zemszał, Piotr (Papers in Linguistics, 2021)
One of the important subjects discussed in discourse texts of the Russian radical Orthodox Church and monarchist movement is the area of man’s sexual and family life, including the issue of homosexuality. In the studied materials, resources describing homosexual people are relatively scarce. Four nominations having a negative meaning of different degree of intensity (гомосексуалист, лесбиянка, содомит, педераст) are used regularly. Against their background, the borrowed nomination гей functions in quite specific way. Out of 29 its uses, only in 11 cases it appears without quotation marks or not as a reported speech. It is a component considered foreign, or even hostile to the studied discourse, perceived as a representation of THEIR understanding of the issue of homosexuality.